2008
DOI: 10.1128/aem.01758-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Affecting Hydrogen Sulfide Formation inSaccharomyces cerevisiae

Abstract: A screen of the Saccharomyces cerevisiae deletion strain set was performed to identify genes affecting hydrogen sulfide (H 2 S) production. Mutants were screened using two assays: colony color on BiGGY agar, which detects the basal level of sulfite reductase activity, and production of H 2 S in a synthetic juice medium using lead acetate detection of free sulfide in the headspace. A total of 88 mutants produced darker colony colors than the parental strain, and 4 produced colonies significantly lighter in colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 48 publications
10
74
0
2
Order By: Relevance
“…We confirm here that H 2 S production strongly depends on sulfur supply, not on differences in the biosynthesis pathway. In wine, where sulfate is predominant, H 2 S is produced through the sulfate assimilation pathway (30,31). In contrast, in cheese, where sulfur is retrieved mainly in methionine and cysteine, the production of H 2 S could arise from cysteine catabolism (9,32).…”
Section: Discussionmentioning
confidence: 99%
“…We confirm here that H 2 S production strongly depends on sulfur supply, not on differences in the biosynthesis pathway. In wine, where sulfate is predominant, H 2 S is produced through the sulfate assimilation pathway (30,31). In contrast, in cheese, where sulfur is retrieved mainly in methionine and cysteine, the production of H 2 S could arise from cysteine catabolism (9,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is hypothesized that under the anaerobic conditions experienced during fermentation, cysteine concentrations may play a more important regulatory role in sulfate reduction (Linderholm et al 2008). It has been shown that yeast respond to the addition of cysteine by increasing the production of H 2 S in preference to methionol while the addition of methionine results in an increase in methionol in preference to H 2 S (Moreira et al 2002).…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 99%
“…Hydrogen sulfide production varies across yeast strains and with the nitrogen status of the juice (Acree et al 1972, Schutz and Kunkee 1977, Giudici and Kunkee 1994, Rauhut et al 1996, Jiranek et al 1995, Sea et al 1998, Bell and Henschke 2005, Linderholm et al 2008, Kumar et al 2010. It is generally understood that the addition of nitrogen, in the form of amino acids, with the exception of cysteine, or ammonium, reduces the production of H 2 S by yeast.…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…A screen of the deletion set of S. cerevisiae strains showed four possible mutations resulting in white colonies, and the relevant genes all encoded components of sulfite reductase (22) and were therefore candidate genes for the mutation in UCD932. The sulfite reductase enzyme complex is composed of catalytic and regulatory subunits.…”
Section: Formation Of Hydrogen Sulfide (H 2 S) Bymentioning
confidence: 99%